The Kyai as the Satria Piningit: The Transformation of Javanese Mythology in Contemporary Socio-Religious Practice - Abdul Somad; Ahmad Basuni; Zarkoni; Babun Suharto (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2025)
This study explores the symbolic, digital, and sociopolitical dimensions of kyai leadership in contemporary pesantren culture, focusing on how the figure of the kyai is framed through the lens of the Javanese Satria Piningit archetype, digital media virality, and community crisis management. Using a qualitative phenomenological approach, data were collected from 31 informants consisting of santri, alumni, community leaders, and pesantren administrators across three pesantren in East Java. The findings reveal that the kyai is widely perceived not merely as a religious authority but as a symbolic embodiment of hidden moral leadership. Informants consistently described the kyai as humble, spiritually ascetic, and quietly influential—traits strongly aligned with the cultural memory of the Satria Piningit. The second finding shows that kyai leadership in the digital era is shaped by dynamics of visibility, viral content, and moral representation. Participants noted that social media platforms often amplify both the authority and vulnerability of the kyai, creating a dual pressure to maintain authenticity while navigating online controversies. The third finding demonstrates that pesantren communities rely heavily on the kyai during moral, social, and political crises; the kyai becomes a stabilizing moral compass whose decisions significantly influence community cohesion. Overall, this study concludes that kyai leadership today is a hybrid model that combines spiritual charisma, cultural symbolism, and digital-era moral negotiation. These findings contribute to a deeper understanding of religious leadership in Southeast Asian Muslim communities and illustrate how traditional authority adapts within modern sociotechnical environments..